PENGARUH TAYANGAN POLISINE INYONG TERHADAP KESADARAN KAMTIBMAS DI BANYUMAS - Rida Purnama Sari; Nuryanti; Agoeng Nugroho (Kinesik, 2023)
This research is entitled The Influence of Polisine Inyong Films on Awareness of Public Security and Order in Banyumas. The aim of this research is first to determine and analyze the influence of the cognitive component on public security and order awareness. Second, to find out and analyze the influence of the affective component on public security and order awareness. Third, to find out and analyze the influence of the conative component on public security and order awareness. Fourthly, to determine the influence of cognitive, affective and conative components together on awareness of Kamtibmas. Fifth, to find out the variables that have the most influence on awareness of Public Order and Security in Banyumas Regency. The sample used in this research was 100 people. The research sample was determined using the proportional sampling method. The analytical tool used is multiple linear regression analysis. The results of the research show that there is an influence of cognitive, affective and conative components partially or jointly on awareness of Kamtibmas. The conative component variable is the variable that has the highest beta coefficient, namely 0.664 compared to the cognitive component variable of 0.444 and the affective component of 0.472.